2018
DOI: 10.1039/c8cc06324a
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free multinitrogenation of amides by C–C bond cleavage: a new approach to tetrazoles

Abstract: A metal-free brand-new one-pot multinitrogenation of amides for the chemo- and regioselective synthesis of 1,5-disubstituted tetrazoles has been developed. By means of electrophilic amide activation, and further C-C bond cleavage and rearrangement, a diverse set of functionalized 1,5-DST derivatives were selectively constructed under mild conditions. As showcased in the mechanisms, the chemoselectivity is easily switched by the selection of the starting materials in the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Solvents for the synthesis of substrates were dried over Molecular Sieves 4A (Wako) prior to use. Rh­(III) complexes [Cp E RhCl 2 ] 2 , 1a , and 1b , benzamides 2a , 2b , 2e , 2f , 2g , 2h , and 2i , and alkene 3c have already been reported. All other reagents were obtained from commercial sources and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Solvents for the synthesis of substrates were dried over Molecular Sieves 4A (Wako) prior to use. Rh­(III) complexes [Cp E RhCl 2 ] 2 , 1a , and 1b , benzamides 2a , 2b , 2e , 2f , 2g , 2h , and 2i , and alkene 3c have already been reported. All other reagents were obtained from commercial sources and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the groups of Charette, Maulide, and Huang have published numerous related works on amide modification and transformation atop this foundation. On the basis of a long-standing interest, our group has also employed the Tf 2 O-activated amide in the crucial process of producing high-bioactivity organic skeletons . Mechanistic research has demonstrated that the keteniminium ion with a high electrophilic reactivity was generated when the amides were activated by Tf 2 O and pyridines (Scheme ).…”
mentioning
confidence: 99%
“…The use of trimethylsilyl azide (TMSN 3 ) instead of hydrazoic acid for many transformations has gained attention since TMSN 3 is less hazardous [26,27]. Some recent studies employ this reagent in the Schmidt synthesis of tetrazoles from ketones that are smaller in size and simpler than the steroidal ketones in this work [28,29]. For the synthesis of steroidal tetrazoles, most often 1,3-dipolar cycloadditions are being used.…”
Section: Introductionmentioning
confidence: 99%